Pathogens in COPD Acute Attack and the Relation Between Pulmonary Function Parameters - Erdem, Ebru; Muz, Mehmet Hamdi; Kirkil, Gamze; Turgut, Teyfik; Deveci, Figen; Akbulut, Handan (Aves, 2011)
Aim: Chronic obstructive pulmonary disease (COPD) is a disease charactarized by the restriction of airflow with no full reversibility. Acute exacerbations often require hospital admissions and hospitalizations. Determining the frequency of viral and atypical patogens in hospitalized patients with acute exacerbations of COPD and to investigate the relationship between these pathogens and parameters of lung function tests is aimed. Material and Methods: Thirty patients with COPD attack and 30 healty volunteers were included in the study. Five mililiters of venous blood sample was taken on the first day and fourth week of hospitalization in COPD group, and once in control group. Sera were tested for IgM and IgG antibodies to Mycoplasma pneumonia, Legionella pneumophila, Chlamydia pneumoniae, respiratory syncytial virus (RSV), influenza A, adenovirus. All cases underwent pulmonary function tests. Results: IgM antibody titers of different pathogens were positive in COPD group. IgG antibody titers to M. pneumoniae were positive in 6 patients (20%), RSV in 26 (86,6%), C. pneumoniae in 22 (73,3%), Adenovirus in 28 (93,3%), influenza A in 18 (60%). There was no IgG antibody positivity to L. pneumophila in COPD group. IgG antibody titers to Influenza A were significantly higher in COPD group than controls (chi(2)=5,455, p=0,020). Antibody titers to other pathogens were similiar in both groups. When we investigated the relationship between lung function parameters and pathogens responsible for acute exacerbations of COPD, no statistically significant difference was found in FEV1, FEV1/FVC values between groups. Conculation: In conclusion, viruses and atypical pathogens have important roles for acute exacerbations of COPD, but no significant relationship was found between pathogens and airway obstruction.
Keywords: atypical pathogens; COPD acute exacerbation; lung function test; virus